Korupsi, Indikator Makro Ekonomi, dan IPM terhadap Tingkat Kemiskinan di Indonesia - Samputra, Palupi Lindiasari; Munandar, Adis Imam (Jurnal Ekonomi Kuantitatif Terapan, 2019)
This study aims to identify the factors causing the poverty rate in Indonesia, both positive and negative impacts. There are three variables used in this study including HDI (Human Development Index), corruption (the amount of convicted corruption), and macro-economic indicators (inflation, GDP per capita, population).The variable of macro-economic indicators functioned as the control variable. To his study used panel data method consisting of the data from 2009 to 2013of 28 provinces in Indonesia. The model of poverty in Indonesia can be explained by Fixed Effect GLS model after passing the model selection and classic assumption collision testing. The results showed that among the three indicators, only the variable of GDP per capita having an insignificant effect on the poverty rate. Other factors have significant effects on thepoverty rate. There are two effects including positive and negative effects. The factors with the ability to reduce the poverty rate in Indonesia areHDI (greater effects in the provinces outside Sumatra and Java-Bali), inflation and population. Only the variable of corruption have a positive effect on the increasing poverty rate in Indonesia. The government needs to actively realize the alleviation of poverty program through human development in all provinces of Indonesia.